A CHALLENGES OF NEOLIBERALISM IN ADDRESSING THE CLIMATE EMERGENCY: PERSPECTIVES FROM ARGENTINE JOURNALISM - Malvina Eugenia Rodríguez (Journal Of Education, 2026)
The article examines how neoliberalism shapes journalistic coverage of the climate emergency in Argentina. Using Critical Discourse Analysis, it compares eight articles from four media outlets — two mainstream (La Nación and La Voz del Interior) and two alternative (Página 12 and La Nueva Mañana) — focusing on two specific cases: Argentina’s withdrawal from COP29 in November 2024 and the Bahía Blanca floods in March 2025. The findings reveal a marked editorial divergence. Mainstream media favour technical or diplomatic framings, minimize state accountability, and treat climate change as secondary to political developments. Alternative outlets, by contrast, politicize the environmental crisis, amplify the voices of affected communities, and explicitly challenge the extractives model and governmental inaction.The paper concludes that Argentine journalism is far from monolithic: it reflects an ongoing tension between hegemonic and counter-hegemonic logics in the construction of climate discourse. In this context, independent and critical journalism plays a strategic role in exposing the structural roots of environmental vulnerability, even as it operates at a significant disadvantage within a media landscape dominated by large commercial conglomerates